Assessment of MALDI-TOF MS as Alternative Tool for Streptococcus suis Identification - Pérez-Sancho, Marta; Vela, Ana Isabel; García-Seco, Teresa; Gottschalk, Marcelo; Domínguez, Lucas; Fernández-Garayzábal, José Francisco (Frontiers in Public Health, 2015)
The accuracy of matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS) for identifying Streptococcus suis isolates obtained from pigs, wild animals and humans was evaluated using a PCR-based identification assay as the gold standard. In addition, MALDI-TOF MS was compared with the commercial multi-tests Rapid ID 32 STREP system. From the 129 S. suis isolates included in the study and identified by the molecular method, only 31 isolates (24.03%) had score values ≥2.300 and 79 isolates (61.24%) gave score values between 2.299-2.000. After updating the currently available S. suis MALDI Biotyper database with the spectra of three additional clinical isolates of serotypes 2, 7 and 9, most isolates had statistically significant higher score values (mean score: 2.65) than those obtained using the original database (mean score: 2.182). Considering the results of the present study, we suggest using a less restrictive threshold score of ≥2.000 for reliable species identification of S. suis. According to this cut-off value, a total of 125 S. suis isolates (96.9%) were correctly identified using the updated database. These data indicate an excellent performance of MALDI-TOF MS for the identification of S. suis.